A test of Bergmann's rule in the Early Triassic: Latitude, body size, and sampling in Lystrosaurus - Kulik, Zoe; Sidor, Christian (Zenodo, 2022)
The ecogeographical rule known as Bergmann's rule suggests that there is a positive relationship between body size and latitude when comparing closely related taxa. The underlying mechanism, or mechanisms, to explain this pattern vary as widely as the taxa that seem to follow it, which has led to skepticism over whether Bergmann's rule should be considered a rule at all. Despite this, Bergmann's rule is widespread among modern birds, mammals, beetles, and some amphibians, but far fewer extinct taxa have been subjected to tests of Bergmann's rule. To test whether Bergmann's rule is detected in extinct taxa, we compared body size proxies in Lystrosaurus recovered from Early Triassic-aged strata in Antarctica, South Africa, India, and China. Our results reveal that average body size is largest at mid-northern paleolatitudes (~45°N) instead of the highest southern paleolatitudes (~70°S). Additionally, maximum body size is consistent across northern and southern hemispheres, indicating that Bergmann's rule did not apply for Lystrosaurus during the Early Triassic. To test potential sample size biases in our results, we used rarefaction and subsampling to show that only the Karoo Basin is well sampled, and that large individuals are exceedingly rare except in the Turpan-Junggar Basin of Xinjiang, China. Taken together, our results suggest that Lystrosaurus had the potential to reach large body sizes in each of the latitudinally widespread tectonic basins studied here, but that local conditions may have allowed individuals at mid-northern paleolatitudes a greater chance of reaching large size compared to southern congeners that suffered increased mortality at young/small sizes. This Excel spreadsheet can be opened in spreadsheet applications that use the OpenDocument Spreadsheet format. Funding provided by: Nick Simons Foundation Crossref Funder Registry ID: http://dx.doi.org/10.13039/100016620 Award Number: EAR 1713787 Funding provided by: Nick Simons Foundation Crossref Funder Registry ID: ...